Teacher translanguaging in CLIL primary education: do teachers' perceptions match their real practices? (Translingüismo y aprendizaje integrado de contenidos y lengua extranjera (AICLE) en la educación primaria: percepciones y prácticas reales del profesorado). Issue 2 (3rd April 2022) - Serra, Judit; Feijoo, Sara
ABSTRACT: The use of the students' first language (L1) in the foreign language class (FL) is a common but controversial issue that has received little attention. This might be more relevant in the case of Content and Language Integrated Learning (CLIL), since, under CLIL approaches, students need to acquire content through an FL that they have not mastered yet. The current paper aims at analysing teachers' uses and perceptions of translanguaging in CLIL classrooms in a primary education context following a case study. Five CLIL primary education teachers from Catalonia participated in the study. They were voice-recorded for several sessions teaching a subject in CLIL with the same class and they also completed a questionnaire. The analysis showed that all the participants used their L1 for a number of purposes. Even though individual perceptions differed, in general, teachers were positive about using translanguaging. CLIL teachers would benefit both from reflecting on their own practices in terms of translanguaging uses and from formal instruction in the matter.